CARIBCAN : Canadian programs for Commonwealth Caribbean trade, investment and industrial cooperation ([CIDA] OttawaCA, 1988)
Outlines the main elements of CARIBCAN and other requirements for imports into Canada. Discusses support for Canadian investment and complementary support for CARIBCAN. Annexes contain inter alia, a list of products excluded from duty free treatment under CARIBCAN, and names and addresses of associations and government agencies in Canada and in the region which can assist in promoting trade investment and industrial cooperation between Canada and the Commonwealth Caribbean.
IDS